ANALISIS PREFERENSI KONSUMEN MILLENNIAL DALAM BERBELANJA DI TOKO KONVENSIONAL, DEPARTMENT STORE DAN E-COMMERCE - odekamaru, Juliam c (Universitas Sam Ratulangi, 2019)
This research is aimed at analyzing product relations, price, place / distribution and promotion of millennial consumer preferences in purchases at Conventional Stores, Department Stores and E-Commerce. The results of this study found facts, 1) Responded in general to have the preference to assume promotion represented an important factor in valuation or purchase in Conventional Stores (55%), as a whole followed by price factors (35%), products (7%) and place / distribution (3%), 2) Responded in general to have a preference which considers the place / distribution to be the most decisive factor or purchased in department stores (41.071%), overall followed by product factors (29.167%), price (20.833%)) and promotions (8,929%), and 3) Responded in general to have a preference that considers place / distribution to be the most important factor in evaluating or buying in e-commerce (31,746%), fully related to price factors (28,571%), ( 20,6357%) and promotions (19,048%).Keywords: Millennial Consumers, Conventional Stores, Department Stores, E-commerce, Conjoin Analysis